Letter (copy) : Food for Spanish Workers - Tewson, Vincent
011-0087-001 HVT / EAB / 802 INTERNATIONAL. 2nd June 1937 Mr. G. Stolz, International Federation of Trade Unions, 9, Avenue d'Orsay, Dear Comrade Stolz, FOOD FOR SPANISH WORKERS We are contemplating sending a further supply of food-stuffs - some 60 tons - to our comrades in Spain, and it is probable that this will be despatched about the middle of this month to Santander. It is desired, however, that this consignment should be earmarked for the Asturian miners, and I shall be extremely glad to know whether you can supply us with the name and address of an Asturian comrade to whom we could consign the goods. With best wishes, Yours sincerely, Assistant Secretary, 292/946/11/87